Pengaruh Pendidikan Dan Pelatihan (Diklat) Dan Kedisiplinan Terhadap Kinerja Pegawai Melalui Pengembangan Karir Sebagai Variabel Intervening (Studi Kasus di Badan Kegawaian, Pendidikan, dan Pelatihan Kota Semarang) - Ningsih, Puspita Jati Dwi; Prabowo, Heri; Nastiti, Prianka Ratri (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2025)
This study aims to analyze the effect of Education and Training (Diklat) and discipline on employee performance, with career development as an intervening variable studied at BKPP Semarang City. Performance includes more than just the achievement of set standards, but also involves the ability possessed by each individual or group to exceed expectations and contribute directly to the achievement of organizational goals. Good performance is reflected in observable and measurable attitudes, which reflect the effectiveness of individuals in carrying out their duties, both in meeting specified standards and exceeding organizational demands in an efficient and effective manner. This research method uses quantitative research. The population used is all civil servants who work at the Semarang City Personnel, Education and Training Agency (BKPP), totaling 64 people. Data collection techniques are using questionnaires and literature studies. This study uses data analysis techniques with structural equation modeling (SEM) methods through SmartPLS 4 software. The results showed that the existence of Education and Training (Diklat) had no direct effect on employee performance at BKPP Semarang City. Education and Training (Diklat) has a significant effect on career development. Discipline has a positive influence on employee performance. Discipline does not have a significant influence on career development. Career development has a positive effect on employee performance. Education and Training (Diklat) affects employee performance through career development. Discipline has no effect on employee performance through career development.